The west and Islam perspective of leadership - AlSarhi, Naji Zuhair; Mohd Salleh, Lailawati; Mohamed, Zainal Abidin; Abdullah, Amini Amir (International Institute for Science, Technology & Education, 2014)
The paper attempts to compare leadership as perceived from the conventional western approach with that of Islam’s. Although it is conceptual and on a viewpoint mode, it is critical in order to pacify some of the western media findings and opinion with regard to the political turmoil in many Islamic countries. Only ten leadership facets are discussed within this paper. Many leaders would adopt the conventional management leadership based on the available literature which was rationally derived through years of research and practices. Undeniably leaders of Muslim countries are guided by the same source. But pious Muslim leaders are also obliged to consider in parallel, guidelines and rules from the revealed sources, namely the Holy Book, Holy Prophet and His Caliphs. Thus leaders with different religion and countries can face the same issues and derive at decisions rationally but yet different.